On the Relationship Between Firms and Their Legal Environment: The Role of Cultural Consonance - Giorgi, Simona; Maoret, Massimo; J. Zajac, Edward (Organization Science, 2019)
In this study we seek to reconcile diverging dominant views on the relationship between firms and their legal environment by offering a cultural contingency perspective. We begin by accepting the notion that a new law will likely exert a powerful influence on targeted firms and that firms’ strategic responses include efforts to shape the impact of the new law. However, we suggest that the success of such response will be contingent on the degree of cultural consonance of firms’ strategic responses and the dominant cultural context at that time. We elaborate this view in our detailed qualitative and quantitative analyses of the automotive Safety Act of 1966 and the response by targeted firms. We provide evidence showing that the changes in the degree of cultural consonance of firms’ strategic response and the predominant cultural beliefs/values explain both the early failure of firms’ efforts to shape the impact of the law in the mid-1960s and the later success by the end of the 1970s. We highlight how firms’ cultural context provides both a constraint and an opportunity for firms seeking to shape legal environmental pressures, and we conclude by discussing the implications of our dynamic contingency perspective for research on law, culture, and strategy.